Photothermally triggered melting and perfusion: responsive colloidosomes for cytosolic delivery of membrane-impermeable drugs in tumor therapy. Issue 7 (1st February 2022) - Ding, Tao; Zhu, Jing; Guan, Haidi; Xia, Daqing; Xing, Yuxin; Huang, Jixi; Wang, Zhenqiang; Cai, Kaiyong; Zhang, Jixi
Abstract : Photothermally triggered cytosolic delivery of membrane-impermeable drugs was achieved by polydopamine nanoparticle-stabilized colloidosomes, paving a new avenue for remotely controlled transportation of drugs through biological membrane barriers. Abstract : A cell membrane barrier which dominates the therapeutic efficacy and systemic side effects is a major bottleneck in the field of drug delivery. Herein, a therapeutic system capable of photothermally triggered on-demand and cytosolic delivery was achieved by polydopamine (PDA) nanoparticle-stabilized colloidosomes. An organic phase change material (PCM, saturated fatty acids) was employed as the lipid core for Pickering emulsification and drug encapsulation, and arginine was utilized as a linker to induce the directional interactions between nanoemulsion droplets and heterogeneously nucleated PDA nanoparticles. Moreover, the PDA particle stabilizers concomitantly mediated the grafting of hydrophilic polymer PEG to further improve dispersibility. The resultant colloidosomes after cooling possess lowered melting points and superior dispersion stability over 7 days. When irradiated with near-infrared light (808 nm), sequential processes of fatty acid melting and direct drug perfusion into the cytosol took place within 10 min. The employment of vorinostat (SAHA, histone deacetylase inhibitor) as a model membrane-impermeable drug resulted in remarkable enhancement of anti-cancer effects both in vitro (5.2 fold reduction in IC50) and in vivo (7.3 fold increase in tumor inhibition rate) with respect to the free drug. The remotely triggered transformable nanoplatform paves a new avenue of responsive and efficient cytosolic perfusion to overcome biological membrane barriers on the basis of colloidosomes.